2006
DOI: 10.2332/allergolint.55.279
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Suppresses Histamine Synthesis by Repressing both Transcription and Activity of HDC in Allergic Rats

Abstract: These findings indicate that increased synthesis of histamine through up-regulation of HDC gene expression and HDC activity in nasal mucosa plays an important role in the development of nasal hypersensitivity. Repression of HDC gene expression and HDC activity by dexamethasone may underlie its therapeutic effect in the treatment of allergy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 35 publications
1
32
1
Order By: Relevance
“…As histidine decarboxylase (HDC) is the only enzyme that synthesizes histamine from histidine in mammals, control of HDC activity is another important target for regulation of histamine signaling. It was reported that HDC mRNA, HDC activity, and the histamine content were significantly increased in the nasal mucosa of TDI-sensitized rats (13). These findings suggest that H1R and HDC genes are allergic disease-sensitive genes and the levels of H1R and HDC expression affect the severity of allergic symptoms, and also that compounds that suppress histamine signaling are promising as anti-allergic drugs.…”
Section: A Llergic Rhinitis (Ar)mentioning
confidence: 73%
See 4 more Smart Citations
“…As histidine decarboxylase (HDC) is the only enzyme that synthesizes histamine from histidine in mammals, control of HDC activity is another important target for regulation of histamine signaling. It was reported that HDC mRNA, HDC activity, and the histamine content were significantly increased in the nasal mucosa of TDI-sensitized rats (13). These findings suggest that H1R and HDC genes are allergic disease-sensitive genes and the levels of H1R and HDC expression affect the severity of allergic symptoms, and also that compounds that suppress histamine signaling are promising as anti-allergic drugs.…”
Section: A Llergic Rhinitis (Ar)mentioning
confidence: 73%
“…We demonstrated previously that repeated intranasal application of TDI induced release of histamine from mast cells via neurogenic inflammation and led to the development of nasal hypersensitivity in guinea pigs and rats (9 -11). Up-regulation of H1R at both the mRNA and protein level was also observed in the nasal mucosa of TDI-sensitized nasal allergic model rats (12,13). As histidine decarboxylase (HDC) is the only enzyme that synthesizes histamine from histidine in mammals, control of HDC activity is another important target for regulation of histamine signaling.…”
Section: A Llergic Rhinitis (Ar)mentioning
confidence: 99%
See 3 more Smart Citations